2005
DOI: 10.1037/0096-3445.134.1.10
|View full text |Cite
|
Sign up to set email alerts
|

Depressive Realism and Outcome Density Bias in Contingency Judgments: The Effect of the Context and Intertrial Interval.

Abstract: The perception of the effectiveness of instrumental actions is influenced by depressed mood. Depressive realism (DR) is the claim that depressed people are particularly accurate in evaluating instrumentality. In two experiments, the authors tested the DR hypothesis using an action-outcome contingency judgment task. DR effects were a function of intertrial interval length and outcome density, suggesting that depressed mood is accompanied by reduced contextual processing rather than increased judgment accuracy. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
182
3
5

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 102 publications
(200 citation statements)
references
References 38 publications
(98 reference statements)
10
182
3
5
Order By: Relevance
“…Since Alloy and Abramson's seminal work in 1979, depressive realism has been a fertile research area and has provided interesting discussions among scientists (e.g., Ackermann & DeRubeis, 1991;Allan et al, 2007;Alloy & Clements, 1992;Haaga & Beck, 1995;Matute, 1996;Msetfi et al, 2005). We have proposed that differential probability of responding, as a function of mood, plays a relevant role in depressive realism: In contrast to nondysphoric individuals, who tend to respond as much as they can to obtain a desired outcome, depressive individuals are more passive, and this provides them with more comprehensive exposure to what happens both when they respond as well as when they do not respond.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since Alloy and Abramson's seminal work in 1979, depressive realism has been a fertile research area and has provided interesting discussions among scientists (e.g., Ackermann & DeRubeis, 1991;Allan et al, 2007;Alloy & Clements, 1992;Haaga & Beck, 1995;Matute, 1996;Msetfi et al, 2005). We have proposed that differential probability of responding, as a function of mood, plays a relevant role in depressive realism: In contrast to nondysphoric individuals, who tend to respond as much as they can to obtain a desired outcome, depressive individuals are more passive, and this provides them with more comprehensive exposure to what happens both when they respond as well as when they do not respond.…”
Section: Discussionmentioning
confidence: 99%
“…Those with a direct score of 9 or above were included in the dysphoric group, whereas participants who scored below 9 were assigned to the nondysphoric group. This cutoff point was the same already used in many other studies about depressive realism (e.g., Alloy & Abramson, 1979;Msetfi et al, 2005) and implies not a clinical categorization but, rather, a common way to identify mildly depressed individuals among a typical population of college students (this is the reason why we prefer to use the term dysphoric instead of depressed). This resulted in the classification of 41 participants as nondysphoric and 25 as dysphoric.…”
Section: Participants and Apparatusmentioning
confidence: 99%
See 1 more Smart Citation
“…contextual processing during cognitive tasks (Msetfi, Murphy, Simpson, & Kornbrot, 2005), and this inflexibility may be related to the high levels of internal attention seen in maladaptive rumination (Nolen-Hoeksema, Wisco, & Lyubomirsky, 2008). There is meta-analytic evidence that emotional inflexibility prospectively predicts poorer courses of depression (Morris, Bylsma, & Rottenberg, 2009), and increased stimulus-appropriate emotional reactivity -even to negative stimuli -prospectively predicts recovery from depression (Rottenberg, Salomon, Gross, & Gotlib, 2005).…”
Section: Resilience In Remission 17mentioning
confidence: 99%
“…Many experiments conducted with this or related tasks have found that even in situations in which there is no statistical relationship between the cue and the outcome, the participants still report that such a relationship exists if the outcome occurred in many trials (Allan & Jenkins, 1983;Allan, Siegel, & Tangen, 2005;Blanco, Matute, & Vadillo, in press;Musca, Vadillo, Blanco, & Matute, 2010). This outcome-density effect also takes place in situations in which participants are not judging the relationship between a neutral cue and an outcome, but the relationship between their own behavior and a consequence (Alloy & Abramson, 1979;Matute, 1995;Msetfi, Murphy, Simpson, & Kornbrot, 2005;Shanks, 1985Shanks, , 1987.…”
mentioning
confidence: 99%